2021
DOI: 10.2478/rjim-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 (IL-10) 1082 promoter polymorphisms and plasma IL-10 levels in patients with bacterial sepsis

Abstract: Background. Interleukin-10 (IL-10) is a multifunctional cytokine has been seen to play a relevant role in the pathogenesis of sepsis. We examined the association between a single nucleotide polymorphism (SNP) in IL-10 -1082G/A in patients with sepsis in Cali city.Methods A total of 100 patients with sepsis and 50 control subjects were enrolled in this study. Blood samples were collected from all patients in EDTA containing tubes. IL-10-1082G/A gene promoter polymorphism was analyzed by Sequence Specific Polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In recent years, a correlation between IL-10 genetic polymorphism and various disease risks has been reported, including tuberculosis, 21 periodontitis, 22 and bacterial sepsis. 23 In addition, the correlation between IL-10 genetic polymorphism and bone mineral density and OP risk has also been reported in many populations, including South Korea, 19 Turkey, 16 Taiwan, 18 and Chinese postmenopausal women. 24 Studies have reported the association of IL-10-rs1554286, -rs1518111, -rs3024490, and -rs1800871 with susceptibility to Behcet's disease, 25 tuberculosis, 26 systemic lupus erythematosus 27 or breast cancer.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, a correlation between IL-10 genetic polymorphism and various disease risks has been reported, including tuberculosis, 21 periodontitis, 22 and bacterial sepsis. 23 In addition, the correlation between IL-10 genetic polymorphism and bone mineral density and OP risk has also been reported in many populations, including South Korea, 19 Turkey, 16 Taiwan, 18 and Chinese postmenopausal women. 24 Studies have reported the association of IL-10-rs1554286, -rs1518111, -rs3024490, and -rs1800871 with susceptibility to Behcet's disease, 25 tuberculosis, 26 systemic lupus erythematosus 27 or breast cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Another study found that polymorphisms in genes resulting in high TNF‐α and low IL‐10 production were associated with higher rates of sepsis in patients with AH 25 . In the context of sepsis, IL‐10 is higher in non‐survivors compared to survivors 26 and polymorphisms associated with high IL‐10 production are associated with higher risk of bacterial sepsis 27 . These conflicting results show the challenges of interpreting the biological relevance of IL‐10 in AH.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In the context of sepsis, IL‐10 is higher in non‐survivors compared to survivors 26 and polymorphisms associated with high IL‐10 production are associated with higher risk of bacterial sepsis. 27 These conflicting results show the challenges of interpreting the biological relevance of IL‐10 in AH. Further confirmatory studies are needed to evaluate the association between IL‐10 and infection in AH.…”
Section: Discussionmentioning
confidence: 99%
“…The signi cant difference between IL-10 gene variants and Hb levels may be attributable to the fact that polymorphisms in the IL-10 gene in uence the expression and function of IL-10.IL-10 is an antiin ammatory cytokine that inhibits immune cells and in ammatory responses to infections. The IL-10 gene is located on chromosome 1 and has several known SNPs, with rs1800872 being the most studied [23,28]. At this locus, there are three genotypes: CC, CT, and TT, with TT being associated with elevated IL-10 levels.…”
Section: Discussionmentioning
confidence: 99%